Highly stable bilayer of LiPON and B2O3 added Li1.5Al0.5Ge1.5(PO4) solid electrolytes for non-aqueous rechargeable Li-O2 batteries. (1st May 2016) - Jadhav, Harsharaj S.; Kalubarme, Ramchandra S.; Jadhav, Arvind H.; Seo, Jeong Gil
Graphical abstract: Highlights: LiPON thin film deposited by RF-sputtering technique. The effect of deposition temperature on ionic conductivity was investigated. The LiPON/B-LAGP composite was successfully employed in Li-O2 battery. LiPON interlayer enhances stability of B-LAGP in contact with Li-metal. Abstract: Lithium ion conducting membranes are barely studied, although they are essentially indispensable for building Li-air batteries composed of aqueous and non-aqueous electrolytes for long-term operation. Lithium phosphorous oxynitride (LiPON) thin films were deposited by RF-sputtering technique on B2 O3 -added lithium aluminum germanium phosphate (B-LAGP). Compact thin amorphous LiPON layer could act as a protective interlayer for B-LAGP by separating it from Li metal electrode and mitigate the reaction between them. Large electrochemical stability window (0–5 V) of LiPON/B-LAGP solid electrolyte shows promising feasibility for applications in all lithium based batteries. The aprotic Li-O2 cell with protected lithium electrode configuration employing LiPON/B-LAGP solid electrolyte has exhibited reasonable cycling stability with long-life of 52 cycles at a limited capacity of 1000 mA h g −1 .